2019
DOI: 10.1097/brs.0000000000002768
|View full text |Cite
|
Sign up to set email alerts
|

Functional Balance Testing in Cervical Spondylotic Myelopathy Patients

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…The existence of poor balance and functional performance in individuals with DCM before surgical intervention has been reported by several studies (Nardone et al, 2008;Yoshikawa et al, 2008;Haddas et al, 2018b). Our study further demonstrated residual balance instability and functional impairments in postoperative individuals with DCM.…”
Section: Residual Balance Instability and Functional Impairment Aftersupporting
confidence: 82%
See 1 more Smart Citation
“…The existence of poor balance and functional performance in individuals with DCM before surgical intervention has been reported by several studies (Nardone et al, 2008;Yoshikawa et al, 2008;Haddas et al, 2018b). Our study further demonstrated residual balance instability and functional impairments in postoperative individuals with DCM.…”
Section: Residual Balance Instability and Functional Impairment Aftersupporting
confidence: 82%
“…Several studies have reported balance instability in individuals with spinal disease (Boudreau and Falla, 2014;Hsu et al, 2014Hsu et al, , 2019Wong et al, 2019). Compared with healthy controls, a greater postural sway with increased muscle activation in the trunk and lower extremities was observed during quiet standing in individuals with DCM (Yoshikawa et al, 2008;Haddas et al, 2018b). In addition, delayed neuromuscular recruitment and postural unsteadiness under perturbation were reported in individuals with DCM (Nardone et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…The compression of the spinal cord can cause various neurological symptoms, such as paresthesia, muscle weakness, muscle spasm, and gait disturbance [2]. Moreover, patients with CSM exhibited postural instability compared with healthy adults [3]. Postural instability may result from impairment in proprioception and the integration of the somatosensory system, which is controlled by the neural tract in the spinal cord [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients with CSM exhibited postural instability compared with healthy adults [3]. Postural instability may result from impairment in proprioception and the integration of the somatosensory system, which is controlled by the neural tract in the spinal cord [3, 4]. Postural control is controlled by the sensorimotor system, which is associated with the visual, vestibular, cerebellar, and proprioceptive systems [5] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In hereditary spastic paraplegia, a myelopathy resembling that in ALD, postural body sway was significantly higher than in healthy controls and was correlated with muscle strength in the legs (Marsden and Stevenson, 2013). In cervical spondylotic myelopathy, the most common myelopathy, postural body sway was also increased (Yoshikawa et al, 2008;Haddas et al, 2019b) and improved after decompressive surgery (Haddas et al, 2019a). Although these conditions do not have the same pathophysiology as ALD, they indicate that postural sway could be a useful way to measure myelopathy.…”
Section: Discussionmentioning
confidence: 99%